Transcatheter Paravalvular Leak Closure - Smolka, Grzegorz; Wojakowski, Wojciech; Tendera, Michal (Springer Singapore : Imprint: Springer, 2017)
Representing the first book to offer complete coverage of all related topics, this title provides up-to-date guidance on exactly why, when, and how to perform transcatheter paravalvular leak closure. An international panel of leading experts in the field address the entire spectrum of associated problems, from relevant anatomy, to imaging methods, to implantation techniques, to a comprehensive presentation of clinical data. Specific topics covered in this book include the mechanisms of artificial valve dehiscence, with a focus on local anatomical conditions; data on conservative and surgical treatment; qualification for paravalvular leak closure; multimodality imaging techniques; a step-by-step description of access, device selection and implantation; practical tips and tricks for troubleshooting; and the latest clinical data on transcatheter paravalvular leak closure. The book facilitates the application of contemporary knowledge in clinical cardiology, cardiac surgery, imaging and interventional cardiology in the management of patients with this challenging clinical problem.